Luteal Phase Ovarian Stimulation versus Follicular Phase Ovarian Stimulation results in different Human Cumulus cell genes expression: A pilot study - Chen, Yu-Chen (Int J Med Sci, 2021)
Background: Luteal-phase ovarian stimulation (LPOS) is an alternative in vitro fertilization (IVF) protocol. However, limited data showed the genes expression of cumulus cells (CCs) in LPOS. Therefore, this study aimed to investigate CC genes expression between LPOS and follicular-phase ovarian stimulation (FPOS) in poor ovarian responders (PORs) undergoing IVF cycles. Methods: This was a prospective non-randomized trial (ClinicalTrials.gov Identifier: NCT03238833). A total of 36 PORs who met the Bologna criteria and underwent IVF cycles were enrolled. Fifteen PORs were allocated to the LPOS group, and 21 PORs were allocated to the FPOS group. The levels of CC genes involved in inflammation (CXCL1, CXCL3, TNF, PTGES), oxidative phosphorylation (NDUFB7, NDUFA4L2, SLC25A27), apoptosis (DAPK3, BCL6B) and metabolism (PCK1, LDHC) were analyzed using real-time quantitative PCR and compared between the two groups. Results: The number of retrieved oocytes, metaphase II oocytes, fertilized oocytes, day-3 embryos and top-quality day-3 embryos, clinical pregnancy rates and live birth rates were similar between the two groups except for significantly high progesterone levels in the LPOS group. The mRNA expression levels of CXCL1 (0.51 vs 1.00, p < 0.001) and PTGES (0.30 vs 1.00, p < 0.01) were significantly lower in the LPOS group than in the FPOS group. The LPOS group had significantly lower mRNA expression of NDUFB7 (0.12 vs 1.00, p < 0.001) and NDUFA4L2 (0.33 vs 1.00, p < 0.01) than the FPOS group. DAPK3 (3.81 vs 1.00, p < 0.05) and BCL6B (2.59 vs 1.00, p < 0.01) mRNA expression was significantly higher in the LPOS group than in the FPOS group. Increased expression of PCK1 (3.13 vs. 1.00, p < 0.001) and decreased expression of LDHC (0.12 vs. 1.00, p < 0.001) were observed in the LPOS group compared to the FPOS group. Conclusions: Our data revealed different CC genes expression involving in inflammation, oxidative phosphorylation, apoptosis and metabolism between LPOS and FPOS in PORs. However, the results are non-conclusive; further large-scale randomized controlled trials are needed to validate the results.